2021
DOI: 10.1111/jnu.12641
|View full text |Cite
|
Sign up to set email alerts
|

The Gaps of Healthcare Service Quality in Nurse Practitioner Practice and Its Associated Factors From the Patients’ Perspective

Abstract: Purpose This study investigates the expectations, perceptions, and gaps of the healthcare service quality (HSQ) from the patients’ perspective, and explores the significant demographic and clinical factors associated with the HSQ in nurse practitioner practice (NPP). Design A cross‐sectional design was carried out, with convenience sampling performed under the NPP in Taiwan, from June to November 2016. Methods The Nurse Practitioner Healthcare Service Quality Scale was used to assess the expectations, percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Healthcare Staff had a significant effect on healthcare service quality. These findings align with prior studies [30][31][32].…”
Section: Results Of Fuzzy Ahpsupporting
confidence: 93%
“…Healthcare Staff had a significant effect on healthcare service quality. These findings align with prior studies [30][31][32].…”
Section: Results Of Fuzzy Ahpsupporting
confidence: 93%
“…These include Tob on and Arias (2018; n 5 51) and Asiamah et al (2021;n 5 610); the latter extended SERVQUAL by adding items relating to hospital hygiene and sanitation in Ghana. Others have adapted traditional items to new contexts, for instance, Almuhanadi et al (2020) in Bahrein (n 5 520); Lin et al (2021), in Taiwan (n 5 200); and Hou et al (2019), in Datuan (n 5 350). Moreover, given that the PQ dimension comprises items relating to timeliness, effectiveness, security, tangibles, and equity, and the PCC dimension addresses patient-centred care, we have addressed Arboleda-Arango et al's (2018) call for Colombian surveys that take users' viewpoints into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Others have adapted traditional items to new contexts, for instance, Almuhanadi et al. (2020) in Bahrein ( n = 520); Lin et al. (2021), in Taiwan ( n = 200); and Hou et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, patients age and gender were found to be significant factors affecting the level of the gap in service quality14–16; however, in another studies, those factors did not have any influence on the level of the gap in service quality 17–19. A study conducted in Taiwan to analyse the gaps in healthcare service quality in nurse practitioner practice has found that the source of admission has an association with the level of gap in quality, with admissions from the emergency department recording lower gaps compared with those from outpatient setups 20…”
Section: Introductionmentioning
confidence: 97%